Aplikasi Pencarian Lokasi Masjid Di Kecamatan Ngaliyan Menggunakan LBS ( Location Based Service ) Berbasis Android (Information Technology and Telematics, 2014)
Abstract With powerful  moderenization development of technology becomes increasingly rapid this leads toa lot ofpeople whorely onthe sophisticationofthetechnology in, let alonetechnologycan now beusedinthemobile phonessomuchthat usecell phonesonlytofeel the development oftechnology. A mosque isa placeof worshipforallMuslims, andlook forthe mosquetoworshipwill be hardforpeoplewho have nevercomein the area. Thus the authorsmakethe following applicationso that peoplecan know thelocation of the positionof the mosquein ordernot to be lateforworship. Subject of this researchis to createa searchsystemlayoutofthe mosquepositionandlayoutoftheuser's positionusing the applicationmaking it easier forusers who are notinthe areaof ​​originto locatethe position ofthe existingmosqueinthestripwithout having todrive aroundin the area. Keywords: Search location of mosque in Ngaliyan District